52nd AIAA/SAE/ASEE Joint Propulsion Conference 2016
DOI: 10.2514/6.2016-4828
|View full text |Cite
|
Sign up to set email alerts
|

Facility Effect Characterization Test of NASA’s HERMeS Hall Thruster

Abstract: A test to characterize the effect of varying background pressure on NASA's 12.5-kW Hall Effect Rocket with Magnetic Shielding had being completed. This thruster is the baseline propulsion system for the Solar Electric Propulsion Technology Demonstration Mission (SEP TDM). Potential differences in thruster performance and oscillation characteristics when in ground facilities versus on-orbit are considered a primary risk for the propulsion system of the Asteroid Redirect Robotic Mission, which is a candidate for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 36 publications
(56 reference statements)
0
18
0
Order By: Relevance
“…It is associated with the ease with which electrons travel from the cathode into the thruster. Previous studies [10] have shown that the magnitude of the cathode coupling voltage increases with decreasing background pressure.…”
mentioning
confidence: 81%
“…It is associated with the ease with which electrons travel from the cathode into the thruster. Previous studies [10] have shown that the magnitude of the cathode coupling voltage increases with decreasing background pressure.…”
mentioning
confidence: 81%
“…Subsequent investigations have shown that the canonical presentation of pressure effects did not fully capture the impact. [8][9][10][11][12][13] Moreover, these effects appears in all types of configurations including thrusters with externally mounted cathodes, with internally mounted cathodes, and magnetically shielded thrusters. Due to this extensibility, these effects are critical to understand.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, thruster stability is impacted by pressure effects. 9 Furthermore, it is unclear whether trends observed during the pressure studies continue to hold when the pressure decreases beyond the limits of ground test facilities. A more recent study on the SPT-100, for example, revealed that even when testing was done below the published recommendation of 3×10 −5 torr, the thruster was still sensitive to changing background pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The growth in interest and popularity of HETs has caused a corresponding increase in HET research, testing, and development programs both domestically and internationally [2][3][4]. Despite the similarities among the devices tested and measurements recorded at each of these facilities, the wide range of facility geometries, sizes, materials, and pumping capacities makes it difficult for researchers to compare datasets without the inclusion of facility-dependent corrections [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. It is therefore desirable to develop an understanding of how to quantify facility effects on HET operation and data collection so that facilitydependent testing artifacts can be corrected for and a facilityindependent understanding of the device performance can be achieved.…”
mentioning
confidence: 99%
“…Although several investigations into facility effects exist in the literature, most focus on the role of facility backpressure on plume properties and device operation. Previous studies have shown that increases in facility pressure result in artificial increases in device thrust and efficiency due to neutral ingestion or entrainment [5][6][7][8][9][10][11][12][13][14]16,17,[20][21][22]. Work has also been conducted linking background pressure to parasitic facility effects caused by resonant charge exchange (CEX) collisions.…”
mentioning
confidence: 99%